(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2015)
The world has been so much impressed by Nehru the world statesman and our country by Nehru the freedom fighter and builder of independent India. Sensitive to human suffering, thrilled by the sight and sound of nature in its magnificence and glory, at home in both lonely hills and among men and women, passionate in his anger against violations of human dignity and yet tolerant of human frailties, a philosopher who had to take to a life of action, a world citizen whose main concern was to build his own nation, a creative writer who had to spend the major part of his mature years in government and administration, Nehru was essentially a lonely man and his greatest relaxation was mountains or children or writing.. His writings reflect his sensitive mind and his generous heart, with his passion for justice and love for the country giving colour and fragrance to the thoughts he sought to weave in English prose the extreame leftists attack him that he was no socialist, the extreme rightists attack him that he was not spiritually oriented”.